A comprehensive review and comparison on heatline concept and field synergy principle. (June 2019) - Tao, Wen-Quan; He, Ya-Ling; Chen, Lei
Highlights: The role and function of heat line concept is to visualize the heat transfer path. The role of field synergy principle is to reveal the fundamental mechanism of heat transfer enhancement. None of the two can be used to deduce the other, nor can be derived from the other. Research needs for both heatline concept and field synergy principle are provided. Abstract: A comprehensive review and comparison on heatline concept and field synergy principle have been made based on more than two hundreds of related publications. The major conclusions are as follows. Both heatline concept and field synergy principle are important contributions to the developments of single-phase convective heat transfer theories. The role and function of heat line concept is to visualize the heat transfer path while that of field synergy principle is to reveal the fundamental mechanism of heat transfer enhancement and to guide the development of enhanced structures. None of them can be used to deduce the other, nor none of them can be derived from the other. Hence, there is no problem of mutual remake between them at all. If heatlines are constructed by solving a Poisson equation additional computational work should be done; However, either the synergy number or the synergy angle both can be obtained by using numerical results without additional computational work. Further research needs for both heatline concept and field synergy principle are also provided.